2021
DOI: 10.1177/09636897211019025
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressant Drugs Mitigate Immune Responses Generated by Human Mesenchymal Stem Cells Transplanted into the Mouse Parenchyma

Abstract: It has been widely accepted that mesenchymal stem cells (MSCs) can evade the immune surveillance of the recipient. However, emerging research cast doubt on whether MSCs are intrinsically immune-privileged. Previously, we observed that the transplantation of human MSCs (hMSCs) into the mouse parenchyma attracted a high infiltration of leukocytes into the injection tract. Thus, in order to reduce the immune responses generated by hMSCs, the aim of this study was to assess which immunosuppressant condition (dexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 49 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…Moreover, to increase the translatability of the results, clinically relevant doses and administration routes were used in the study [ 17 , 18 ]. Similar to results previously observed from WT mice [ 4 ], we hypothesized that combined therapy involving the use of more than one immunosuppressant will be effective in reducing immune responses generated via hMSCs injected into the parenchyma of the transgenic AD mouse model.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Moreover, to increase the translatability of the results, clinically relevant doses and administration routes were used in the study [ 17 , 18 ]. Similar to results previously observed from WT mice [ 4 ], we hypothesized that combined therapy involving the use of more than one immunosuppressant will be effective in reducing immune responses generated via hMSCs injected into the parenchyma of the transgenic AD mouse model.…”
Section: Introductionmentioning
confidence: 52%
“…Previously reported procedures were referred to prepare the cells for injection [ 4 , 24 ]. Human Wharton’s jelly-derived mesenchymal stem cells (Human MSCs; hMSCs) were preconditioned with ethionamide (1261004; Invitrogen, Waltham, MA, USA) and were cultivated in T175 flasks (Thermo Scientific, Waltham, MA, USA) containing MEM alpha 1x (MEMα1x) media (12571-071; Gibco, Waltham, MA, USA) supplemented with 10% foetal bovine serum (FBS, S1480; Biowest, Riverside, MO, USA) and 0.5% Gentamicin (15710-072; Invitrogen, USA) at 37 °C, 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations were made up to 24 h in this study because fever subsided after 24 h in the clinical trial. Furthermore, according to studies that we have published recently, very few residual human MSCs were identified in the mouse brain one week following MSC transplantation [16,31,32]. Thus, although not extensively studied, since very few residual human MSCs were present in the mouse brain, signs of inflammatory responses may not have been detected at 1 or even 2 weeks following MSC transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…Despite mounting evidence delineating the importance of inflammation in the stroke pathology, it is poorly described to what extent partial immune deficiency influences the overall stroke outcome. Several immunosuppressed mouse models have been used in preclinical stroke research, most prominent: (a) pharmacological immunosuppression with calcineurin inhibitory drugs (e.g., tacrolimus) that block the development and proliferation of T cells; (b) genetically deficient mice that lack recombination activating gene 2 protein (Rag2 -/- ) required for the generation of mature B and T lymphocytes; and (c) NOD scid gamma (NSG) mice that lack mature T and B lymphocytes, natural killer (NK) cells and have deficiencies in multiple cytokine signalling and innate immunity [11,12]. However, it is unclear to what extent the immunosuppression in these mouse models alter the natural pathology of stroke and may affect the outcome of therapies that require immunosuppression such as human cell-based therapies.…”
Section: Introductionmentioning
confidence: 99%